2014
DOI: 10.1016/j.gca.2014.09.011
|View full text |Cite
|
Sign up to set email alerts
|

Community calcification in Lizard Island, Great Barrier Reef: A 33 year perspective

Abstract: Measurements of community calcification (G net)However, it should be noted that the uncertainty in the live coral coverage estimates in this study and in 1978 were fairly large and inherent to this methodology. Using the reef calcification rate equation while assuming that seawater above the reef was at equilibrium with atmospheric PCO 2 and given that live coral cover had not changed G net should have declined by 30±8% since the LIMER study as indeed observed. We note, however, that the error in estimated G n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
58
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(64 citation statements)
references
References 45 publications
6
58
0
Order By: Relevance
“…The present experiments demonstrate the importance of living organisms on benthic surfaces in maintaining a positive balance between precipitation and dissolution of calcium carbonate. Whereas several reefs around the world are already at the threshold between precipitation and dissolution of calcium carbonate (Silverman et al, 2009(Silverman et al, , 2014, the susceptibility of coral reefs to net dissolution in the future likely will be linked directly to the proportion of the reef covered by macrocalcifiers and sediments. In addition to dissolution, it also is possible that coral reefs will be exposed to increased bioerosion at high pCO 2 (Wisshak et al, 2012;Crook et al, 2013) that will decrease the integrity of the carbonate framework.…”
Section: Discussionmentioning
confidence: 99%
“…The present experiments demonstrate the importance of living organisms on benthic surfaces in maintaining a positive balance between precipitation and dissolution of calcium carbonate. Whereas several reefs around the world are already at the threshold between precipitation and dissolution of calcium carbonate (Silverman et al, 2009(Silverman et al, , 2014, the susceptibility of coral reefs to net dissolution in the future likely will be linked directly to the proportion of the reef covered by macrocalcifiers and sediments. In addition to dissolution, it also is possible that coral reefs will be exposed to increased bioerosion at high pCO 2 (Wisshak et al, 2012;Crook et al, 2013) that will decrease the integrity of the carbonate framework.…”
Section: Discussionmentioning
confidence: 99%
“…For the latter, sustained observations of contemporaneous chemical and ecological conditions in reef and coastal environments provide important data sets to test our understanding of variability and response over time (e.g., Juranek et al, 2009;Alin et al, 2012Alin et al, , 2015Breitburg et al, 2015;Kline et al, 2015), but most time-series datasets do not extend beyond 5 years. Longer-term studies of reef chemistry and ecology are few in number (e.g., Silverman et al, 2012Silverman et al, , 2014 and often characterized by large gaps in time between repeat sampling.…”
Section: Introductionmentioning
confidence: 99%
“…Yet these projections do not eq kg −1 and 707 mol kg −1 respectively ( Fig. 5-2), greater than those measured in water flowing across other coral reefs where CO 2 with similar residence times and bathymetry (Shamberger et al, 2011;Shaw et al, 2014;Silverman et al, 2014;Kline et al, 2015).…”
Section: Carbonate Chemistry and Community Metabolismmentioning
confidence: 66%
“…These studies consistently report correlations between NEC and reef-water Ω , and these relationships are used to forecast when ocean acidification will shift reefs from net accretion to net dissolution (Ohde and van Woesik, 1999;Shamberger et al, 2011;Shaw et al, 2012;Bernstein et al, 2016;Muehllehner et al, 2016). Multi-decade declines of NEC have already been observed on the Great Barrier Reef and attributed primarily to ocean acidification (Silverman et al, 2012(Silverman et al, , 2014. Supporting this assertion, Albright et al (2016) artificially manipulated reef-water pH to levels of the pre-industrial open ocean, and found that NEC increased.…”
Section: Introductionmentioning
confidence: 77%